Modeling and application of a stochastic drag for fibers in turbulent flows - Marheineke, Nicole; Wegener, Raimund (International Journal of Multiphase Flow, 2011)
Considering the dynamics of long slender elastic fibers in turbulent flows, there exists a stochastic aerodynamic force concept for a general drag model based on a k- εlunate turbulence description in literature. In this paper we generalize the concept and formulate an air drag model that is universally valid for all Reynolds number regimes and incident flow directions. The associated turbulent force overcomes the hitherto existing limitations and allows the simulation of all kind of fibers (flexible, stiff, light, heavy) immersed in turbulent flows. Moreover, the comparison of the numerical results with PIV-measurements shows very convincing agreements in the industrial application of technical textile manufacturing. © 2010 Elsevier Ltd.
Keywords: Aerodynamic drag; Data interpolation; Dimensional analysis; Fiber-fluid interactions; Long slender fibers; Numerical simulations; Stochastic partial differential algebraic equation; Turbulence modeling